Evaluación de la evolución económica colombiana con respecto a economías mundiales con énfasis en el entorno latinoamericano : análisis de conglomerados y frontera estocástica para un panel de datos de 1960 a 2015 (2017)
"The purpose of this document is to evaluate Colombian economic environment in relation with the rest of the globe by using macro-economic variables in the years between 1960 and 2015. The analysis is based on a fore-cast made for Colombia until 2050. Then, by using cluster analysis with hierarchical methods adjusting the re-sult with a non-hierarchical method named k-means, the aim of the project is to generate different clusters for each group of countries on a specific year. The main objective of the cluster analysis is to evaluate how lagged is Colombia against others economies in the world." -- Tomado del Formato de Documento de Grado.